Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.pmedr.2017.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Different types of housing and respiratory health outcomes

Abstract: Evidence has shown that housing conditions may substantially influence the health of residents. Different types of housing have different structures and construction materials, which may affect indoor environment and housing conditions. This study aimed to investigate whether people living in different types of housing have different respiratory health outcomes. The data from the 1999–2006 National Health and Nutrition Examination Survey were used for the analyses. The types of housing included houses, townhou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
1
24
1
1
Order By: Relevance
“…The unadjusted expected case density is based purely on child population. We also calculated expected case density taking into account age/sex-specific prevalence reflecting three age classes (<6, [6][7][8][9][10][11][12][13][14][15][16][17][18] and SES by applying the HOUSES-specific AE prevalence.…”
Section: Expected Case Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…The unadjusted expected case density is based purely on child population. We also calculated expected case density taking into account age/sex-specific prevalence reflecting three age classes (<6, [6][7][8][9][10][11][12][13][14][15][16][17][18] and SES by applying the HOUSES-specific AE prevalence.…”
Section: Expected Case Densitymentioning
confidence: 99%
“…4 Likewise, we recently reported that lower SESas measured by the individual-level SES measure HOUSES (HOUsing-based SocioEconomic Status)is an independent risk factor for childhood adversity in the mixed rural-urban community of Olmsted County, Minnesota. 6 Apart from SES, factors associated with the risk of childhood trauma have been reported relating housing or neighborhood characteristics and a number of different topics including health complaints, 7,8 cigarette smoking, dental hygiene, 9 chronic health conditions, 3,10 functional and cognitive impairment, 11 inhalation exposures, 8,[12][13][14][15][16] and infection risk. Scant literature addresses the impact of housing and neighborhoods on health outcomes in a well-defined pediatric population with existing studies focusing on the elderly 11 or high school students.…”
Section: Introductionmentioning
confidence: 99%
“…There is little peer-reviewed literature addressing public health outcomes or related strategies in market-rate multifamily real estate. Current research addressing health in multifamily projects most frequently explores low-income housing topics such as energy efficient retrofits (Underhill et al 2018), particle emissions (Chan et al 2018), and respiratory health outcomes across housing types (Gan et al 2017). While corporate real estate developers specializing in office buildings can cite returns on investments in the form or fewer employee sick days and higher employee retention rates (Klimek 2016), it is more difficult to translate these types of returns into the residential real estate market.…”
Section: Perspectives From Real Estatementioning
confidence: 99%
“…Mobile homes influence health through multiple social mechanisms such as indoor housing risks (e.g. fire, injuries, toxins), unstable housing tenure, and the characteristics of the surrounding neighborhood [15,16]. Households with a larger number of occupants tend to have limited income to spend on housing, low-wage employment opportunities, and higher stress levels [17].…”
Section: Introductionmentioning
confidence: 99%